The Relationship Between Genital Hygiene Attitude and The Incidence of Leukorrhea in Class X Adolescent Girls at SMK Swagaya 1 Purwokerto - Nurul Hidayah; Tin Utami; Siti Haniyah (LPPM Universitas Harapan Bangsa, 2024)
Leukorrhea is a vaginal discharge other than blood that varies in colour, odour and consistency usually caused by a lack of genital hygiene. This study aims to determine the relationship between genital hygiene attitudes and the incidence of leukorrhea in class X adolescent girls at SMK Swagaya 1 Purwokerto. This type of research is quantitative research with descriptive correlative design and cross-sectional approach. This study involved 109 respondents with the criteria of class X female students at SMK Swagaya 1 Purwokerto who were taken by total sampling technique. The results showed that all respondents had a positive attitude (100%) and most respondents experienced normal leukorrhea (74.5%). Spearman ranks statistical test shows that there is a significant relationship between genital hygiene attitude and the incidence of leukorrhea in Class X adolescent girls at SMK Swagaya 1 Purwokerto, with a very weak negative relationship strength (p value: 0.0042; CC= -0.195).